BACHELOR DEGREE PROGRAMS IN INTERNATIONAL RELATIONS AND REGIONAL STUDIES: A COMPETENCE-BASED APPROACH TO PROFESSIONAL TRAINING OF STUDENTS IN FOREIGN LANGUAGES - E. M. Pozdnyakova (Vestnik MGIMO-Universiteta)
The notion of scientific paradigm has taken some time to be accepted by linguists, and eventoday the problem of boundaries of coexisting nowadays linguistic paradigms remains debatable. Althoughmethodological guidelines of a paradigm of scientific knowledge in linguistics have in principle beenworked out, the fact that linguistics is intensively approaching interdisciplinarity entails the appearance ofoverlapping zones “on the boundaries” of linguistic paradigms as well as “on the boundaries” of linguisticsand other cognitive sciences. Cognitive-discursive paradigm offers results of research, devoted to the role oflanguage unfolding in thought. Being both fundamental and experimental, cognitive approach contributessignificantly to the development of applied sciences, in particular to the theory and methodology of languageteaching. The approach gives opportunity to study conceptualization and categorization processes, lexicaland discursive competence in the view of applied teaching goals.The article stresses that cognitive-discursive paradigm:– is increasingly growing in its interdisciplinary nature, thus approaching even closer the EFL teaching;– investigates represented in the language knowledge and experience structures, introducing theexperience of the world around us into lexical competence of EFL students;– considers one of its major tasks further investigation of mental lexicon;– as the discursive practice is becoming even more accessible for EFL students in the course of on-linecommunication, it offers new methods of teaching communication, based on cognitive theory of discourse.